The history of seafaring : navigating the world's oceans - Johnson, Donald S., 1932-; Nurminen, Juha. (London : Conway, 2007)
This is a large-format, meticulously researched, lavishly illustrated and fully international history of mankind's seaborne voyages from the Phoenicians and Chinese to modern navies and round-the-world sailing yachts.
The Dawn of Navigation -- Seafarers of Oceania -- Idea and Art of Pacific Navigation -- Arctic Seafarers -- The First Boats and ships -- The Seafarers Natural World -- understanding the winds -- Comprehending the currents -- Accounting for the tides -- Dealing with the Weather -- Watching the heavens -- Latitude Sailing -- Establishing Location -- Finding Direction -- Natural Phenomenon -- Ancient Sailing Routes and Peripli -- Egyptian voyages to East Africa -- Phoenicians: the first open sea navigation -- From Peripli to Rutters and Sailing Directions -- the Ancient Mediterranean -- Cosmography of the Ancients -- Pythagorean School -- Alexandrian School -- Roman Contributions -- Second Alexandrian School -- Map Projections -- Navigation In the Middle Ages -- New Views in the Medeval World -- Merchant Ships in the Middle Ages -- Dividing the Horizon: From Wind-Rose to Compass Card -- Michael of Rhodes -- Arab Dhow -- Arab Science Spreads Northward -- Indian Ocean -- the Silk Road's Watery Path -- Early Navigation In Northern Waters -- King Arthur of England -- Age of the Saints -- The Enigma of Currents -- The Voyages of Othere and Wulfstan -- Soundings -- Viking Routes and Long Distance Navigation -- Sea Kings of the North -- Winds of the World -- The King's Mirror -- Nicholas of Lynn -- Viking Ships -- Chinese Junks and the Treasure Ships of Zhen He -- Advances In Sciences -- Scientists Open The Skies -- History of the Compass -- Celestial Ephemera for Navigation -- The Mystery of Magnetism -- The Log -- Iberian Ventures In The Atlantic -- Beyond the Pillars of Hercules -- Linking the Atlantic With The Indian Ocean -- From the Quadrant to the Cross-Staff -- Westward, Across the Atlantic Ocean -- Dead Reckoning -- Dividing the Ocean Sea: The Treaty of Tordesillas -- Ships of the Age of Discovery -- From the Art of Navigation to a Technical Science -- Image of the World In Word and Line -- Leading Theorists for a New Discovery -- Plotting the Tides -- The Measurers for a New Cosmography -- From the Astrolabe to the Sextant -- Lighthouses and Seamarks -- By Icey Sea to the Mighty Kingdom of Cathay -- North America: an Impenetrable Barrier -- Beyond Bleak Russia's Northernmost Confines -- Failures Unending Ocean Perils -- From Doctrine and Discovery to a Place on the Map -- The Dutch Flute -- The World Encompassed -- Circumnavigation Succeeded -- Foreign Trade Expanded -- Exploration Continued -- East Indiamen -- From a Sandglass to the Chronometer -- Endeavours Extended -- The Challenge of Longitude -- New Horizons -- Dangerous Ground -- Exploration Ships in the Pacific and the Antarctic -- The Sea on Paper -- Frontiers Unlimited -- New Goals: Scientific Ventures -- The Clipper -- The Ice-choked Seas -- Vega and the First Cargo Steamers -- First Circumnavigation Single-handed -- Epilogue: the Electronic Age.
Includes bibliographical references (pages 367-371) and index.
Keywords: Navigation -- History; Naval art and science -- History; Nautical instruments -- History; Seafaring life -- History